2012
DOI: 10.1371/journal.pone.0041822
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Glandular Trichome Proteins in Artemisia annua L. Using Comparative Proteomics

Abstract: Glandular secreting trichomes (GSTs) are called biofactories because they are active in synthesizing, storing and secreting various types of plant secondary metabolites. As the most effective drug against malaria, artemisinin, a sesquiterpene lactone is derived from GSTs of Artemisia annua. However, low artemisinin content (0.001%∼1.54% of dry weight) has hindered its wide application. We investigate the GST-expressed proteins in Artemisia annua using a comparative proteomics approach, aiming for a better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…In general, the vast majority of proteins identified previously from A. annua by Wu et al were also found in our datasets [ 10 ]. Notably, in the trichome-enriched sample data, we found amongst others a similarly large number of ATPases/ATP synthases and oxidoreductases ( e.g.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…In general, the vast majority of proteins identified previously from A. annua by Wu et al were also found in our datasets [ 10 ]. Notably, in the trichome-enriched sample data, we found amongst others a similarly large number of ATPases/ATP synthases and oxidoreductases ( e.g.…”
Section: Resultssupporting
confidence: 76%
“…The protocol that was applied for the isolation of glandular trichomes is based on the process of glass bead abrasion which has been described previously [ 10 , 15 , 16 ]. In these earlier studies, it was reported that the majority of the cell material enriched by this method represented glandular trichomes albeit with a significant remainder of non-glandular trichomes [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biosynthesis of the volatile organic compounds, that comprise essential oil, has been studied in artemisias (Lu et al, 2002;Kessler et al, 2006;Wu et al, 2012;Bilia et al, 2014;Pratt et al, 2014;Ma et al, 2015 and2017a andSalmon et al, 2015;Shi et al, 2017) and more extensively in a variety of heterologous plant systems, including the model plant species such as Arabidopsis thaliana (Christianson 2001;Rodriguez-Concepcion 2001;Keszei et al, 2008;Degenhardt et al, 2009;Baldwin 2010;Ramak et al, 2014;Lange 2015;Nieuwenhuizen et al, 2015;Tholl 2015;Rehman 2016;Fujita et al, 2017). The information elicited from various aromatic plants collectively suggests that the quantitative variation in the productivity of volatile organic compounds in the site of their synthesis, such as glandular trichomes, depends on the availability of the starting substrates produced by primary metabolism, expression levels of MVA and MEP pathway and downstream genes and catalytic efficiency of the gene products (Estevez et al, 2001;Munoz-Bertomen et al, 2006;Cordoba et al, 2009;Ramak et al, 2014).…”
Section: Genetical Determination Of the Content And Composition Of Armentioning
confidence: 99%